Undue influence - Martini, Steve (Headline Book Pub., 1995)
As lawyer Paul Madriani's wife lies dying, leaving him with two children, she asks a favor: protect her younger sister, Laurel, mired in a bitter child custody battle with her former husband, a powerful state senator. When the senator's new wife is murdered and police arrest Laurel, Madriani sets out to keep his promise and discovers a Laurel no one knew. By the author of Compelling Evidence.